Remote sessions and frequency analysis for improved insight into cerebral function during pediatric and neonatal intensive care. - Lofgren, N. (IEEE Transactions on information technology in biomedicine)
A project involving recording and analysing EEG together with cardiovascular signals and temperature has been initiated. The aim of this project is to establish difficulties and possibilities involved with implementing a system for remote sessions and analysing EEG in correlation with other physiological signals. One objective is to find indicators of cerebral function during postasphyxia neonatal intensive care and pediatric cardiopulmonary bypass surgery with hypothermia. Remote sessions for joint interpretation have been carried out between pediatricians and clinical neurophysiologists, and EEG has been analyzed using frequency analyzing tools. One result is the discovery of reversible spectral changes coinciding with blood pressure falls, which may indicate loss of autoregulation function. This finding is one outcome from initial use of a system, developed during the project to facilitate communication about, and analysis of the recorded signals. Thus, already from a limited number of remote sessions and the use of basic signal processing techniques, important results have been achieved and better insight has been gained of how cerebral function is affected by cardiopulmonary bypass surgery. In this paper, we present our experiences from introducing a system for remote consultations, and evaluate the use for such a system in the current applications.